ETR 300 : Green Island Enterprises / Muhamad Faizal Ibrahim ... [et al.] - Ibrahim, Muhamad Faizal; Mohd Alimin, Nor Azlin; Mukhtar, Rosnida; Abd Hamid, Hasnida Izwani; Masrion, Mohd Naim (2001)
GREEN ISLAND is a business that provides services for agro tourism a.k.a Tropical Fruit Park. This business plan is very potential. It is planning the purpose of a getting a loan and as a guideline to GREEN ISLAND. It is consist of introduction, administration plan, operation plan, marketing plan, and financial plan. In introduction, it gives information about background of partners, partnership agreement and location of business. It state date of commencement and also potential of the business. Location of business it state to narration, what if the future side to choose Langkawi as a location. Besides that, it state together is a complete map of GREEN ISLAND (TROPICAL FRUIT PARK) located. Administration plan is plan that to ensure that the administration and managing the admin is always in a best performance. It is to manage the expenses of the administration. Also how to develop a caliber and able to do a good job, to ensuring the firm is concern about workers welfare. Marketing plan is to plan a promotion in order to attract a customer and allocated a budget for it. Planning a market share and allocate market size as to forecast a sale for 3 years. Target market and market analysis also create to identify the market for our business either is has a great potential or vice versa.